Psychometric Properties of the Icelandic Translation of the Body Appreciation Scale-2 - Þóra Gréta Pálmarsdóttir 1992-; Anna Elísa Karlsdóttir 1992- (2016)
The Body Appreciation Scale-2 is a measure of positive body image, which is a growing field of study in modern society. In this study, the psychometric properties of the Icelandic version of the Body Appreciation Scale-2 were examined in a sample of 905 people. Exploratory factor analysis of the BAS-2 revealed a one factor structure and factor loadings similar to previous research. Predictive and construct validity were tested via correlations between the BAS-2 and six other related measures. Internal consistency of the Icelandic version BAS-2 was good, α = 0.95. As hypothesized the BAS-2 was negatively correlated with internalization of appearance ideals and physical appearance comparison and positively correlated with appearance evaluation, self-esteem, well-being and body-food choice congruence. These results indicate that the Icelandic translation of the BAS-2 is an appropriate measure of positive body image in Iceland. The Body Appreciation Scale-2 (BAS-2) er mælitæki á jákvæðri líkamsímynd, sem er vaxandi rannsóknarsvið í nútíma samfélagi. Í þessari rannsókn eru próffræðilegir eiginleikar íslenskrar útgáfu BAS-2 kannaðar í 905 manna úrtaki. Leitandi þáttagreining á BAS-2 leiddi í ljós einn þátt og svipaðar þáttahleðslur og fundist hafa í öðrum rannsóknum. Forspárréttmæti og hutakaréttmæti voru könnuð með því að skoða fylgnina á milli BAS og sex annara mælinga. Innri stöðugleiki íslenskrar útgáfu BAS-2 reyndist góður, α = 0.95. BAS-2 hafði neikvæða fylgni við innfæringu staðalímynda og útlitssamanburð og jákvæða fylgni við útlitsmat, sjálfsálit, vellíðan og jafnvægi milli líkama og innbyrðingu matar. Niðustöðurnar studdu því tilgátur sem settar voru í upphafi. Í heildina benda niðurstöður til þess að íslenska útgáfan af BAS-2 sé viðeigandi mælitæki fyrir jákvæða líkamsímynd á Íslandi.